Internalization of Islamic Spiritual Values in the Culture of an Excellent School at SMA Negeri 3 Semarang - Samsudin, Arif; Chamami, M. Rikza; Fihris, Fihris (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
Schools often emphasize academic achievement, modern facilities, and global achievements, but often spirituality is not a major concern even though academic intelligence without spiritual guidance has the potential to produce morally fragile graduates. This study aims to analyze the internalization of Islamic spiritual values in the culture of an excellent school at SMA Negeri 3 Semarang, as well as to examine the impact of the Specta Religios and Specta Charity programs on student character development. This research uses a qualitative approach with a descriptive type, through observation, interviews, and documentation techniques of students, PAI teachers, and Rohis extracurricular advisors. The results show that Specta Religi program, which includes reciting the Qur'an, performing the dhuha prayer, and giving religious lectures, has succeeded in fostering religious habits, discipline, and a sense of responsibility among students. Meanwhile, the Specta Charity program, which involves distributing food, social service, and caring activities, has fostered solidarity, empathy, and social responsibility. These two programs complement each other in instilling Islamic values because they emphasize a balance between vertical religiosity towards Allah and horizontal care for others. Thus, the internalization of Islamic spiritual values at SMA Negeri 3 Semarang has proven effective in forming a holistic, excellent school culture, producing students who are both high-achieving and noble in character.